2011
DOI: 10.1021/ja2060116
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Quantification of Nucleic Acids with Large Dynamic Range Using Multivolume Digital RT-PCR on a Rotational SlipChip Tested with HIV and Hepatitis C Viral Load

Abstract: In this paper, we are working toward a problem of great importance to global health: determination of viral HIV and Hepatitis C (HCV) loads under point-of-care and resource limited settings. While antiretroviral treatments are becoming widely available, viral load must be evaluated at regular intervals to prevent the spread of drug resistance, and requires a quantitative measurement of RNA concentration over a wide dynamic range (from 50 up to 106 molecules/mL for HIV and up to 108 molecules/mL for HCV). “Digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
204
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(205 citation statements)
references
References 60 publications
(107 reference statements)
0
204
0
1
Order By: Relevance
“…Few authors, however, have yet investigated the application of this technology to infectious disease diagnostics. Experimental systems have demonstrated proof of principle for quantification of adenoviral genome copies, GB virus in transfected cell culture lines, serial dilutions of hepatitis C virus and HIV RNA, and purified, serially diluted HIV RNA from two clinical samples (19,30,31). The latter studies demonstrated a 4-log 10 -unit linear range and variable agreement with real-time PCR methods.…”
Section: Discussionmentioning
confidence: 99%
“…Few authors, however, have yet investigated the application of this technology to infectious disease diagnostics. Experimental systems have demonstrated proof of principle for quantification of adenoviral genome copies, GB virus in transfected cell culture lines, serial dilutions of hepatitis C virus and HIV RNA, and purified, serially diluted HIV RNA from two clinical samples (19,30,31). The latter studies demonstrated a 4-log 10 -unit linear range and variable agreement with real-time PCR methods.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, smaller droplets allow the isolation of more molecules per volume assayed. If template concentration is highly variable across samples, both small and large droplet reactions can be carried out in parallel to expand the assay dynamic range 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Many of these disadvantages are due to technical limitations that are being addressed by manufacturers who are developing improved commercial instruments and reagents (22,23).…”
Section: Comparison Of Dpcr To Qpcrmentioning
confidence: 99%